SAE Technical Paper Series 2001
DOI: 10.4271/2001-01-0504
|View full text |Cite
|
Sign up to set email alerts
|

Non-Linear Damage Analysis in Accident Reconstruction

Abstract: Frontal, side, rear, pole and offset car to car data sets are examined using familiar damage analysis models: constant stiffness, bilinear stiffness, and force saturation. In addition to these, a non-linear power-law formulation is introduced and compared to the others. The power-law provides a nonlinear stiffness coefficient that transitions between a constant force model and constant stiffness model as the power goes from 0 to 1. It also provides a continuous, single valued function that is easily integrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…The vehicle acceleration increased with speed until a plateau of approximately 300 to 350 m/s2 was reached. This plateau like behavior has previously been described by Campbell (1974) and by Wood et al (1993), and has been modeled in accident reconstruction with the force saturation model (Strother et al 1986) and the power-law model, Woolley (2001).…”
Section: Overlap and Speed Effectssupporting
confidence: 57%
“…The vehicle acceleration increased with speed until a plateau of approximately 300 to 350 m/s2 was reached. This plateau like behavior has previously been described by Campbell (1974) and by Wood et al (1993), and has been modeled in accident reconstruction with the force saturation model (Strother et al 1986) and the power-law model, Woolley (2001).…”
Section: Overlap and Speed Effectssupporting
confidence: 57%
“…This research, based on Campbell's [1] pioneering work, has evolved into analysis procedures such as CRASH [2] and its latterday variants, EDCRASH [3], etc. Other research has shown that generalized non-linear relations and geometric crush shape representations can reflect car crush behaviour for velocity changes up to and over 120 km/h [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In [21], the genetic algorithm is used to compute the model parameter (spring stiffness). The work [22] uses power law model to model the crash and experimental observation is done to obtain the impact attenuator parameters. The work [23] uses simple model of mass-spring to simulate the crash and the spring stiffness is obtained from full-scale experimental data analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the works [21][22][23], the mathematical model of the impact attenuator in this work is built using the first principle as a continuous-time model, i.e., it comprises of mass-spring with an additional damper model. However, different from [21][22][23], we convert the continuous-time model into the discrete-time model using Euler method and we show the exact discrete-time model which is later coded into MATLAB's routine to simulate the problem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation